1997
DOI: 10.1074/jbc.272.6.3669
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of Sulfated Secretogranin II in the trans-Golgi Network of GH3B6 Prolactin Cells

Abstract: Secretogranin II (SgII) is a protein specific to the matrix of the secretory granules in neurons and neuroendocrine cells. We have already demonstrated the precursor-product relationship between sulfated SgII and four N-terminal derived peptides in GH3B6 prolactin cells. In this study, we have investigated the subcellular compartment in which the cleavage of SgII is initiated by taking advantage of its tyrosine sulfation in the transGolgi network (TGN). In order to prevent export of radiosulfated SgII from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…It is interesting that Li et al (26) suggested that the MUC1 cytoplasmic sequence CQC 3 RRKNYGQLD might represent a nuclear localization signal as defined for c-Myc (PAAKRVKLD), where basic residues flanked by neutral residues and the LD motif are all part of the functional signal. They also reported that mutation of RRK 6 to AAA 6 in MUC1 blocks heregulin-dependent nucleolar targeting of MUC1 and ␥-catenin and redirects both proteins to the cytoplasm (26 (86). Mutation of target Cys residues can (i) modulate exit from the endoplasmic reticulum (69,87), (ii) alter steady-state subcellular localization (70,78), (iii) alter specific membrane trafficking steps (66,68,77,81,87), (iv) alter homotypic and heterotypic protein-protein interactions (72,84,88), (v) alter the association with lipid microdomains (82,89), or (vi) alter protein function (71,87,90,91).…”
Section: Muc1 Exhibits Dual Palmitoylation At the Boundary Of The Tramentioning
confidence: 99%
See 3 more Smart Citations
“…It is interesting that Li et al (26) suggested that the MUC1 cytoplasmic sequence CQC 3 RRKNYGQLD might represent a nuclear localization signal as defined for c-Myc (PAAKRVKLD), where basic residues flanked by neutral residues and the LD motif are all part of the functional signal. They also reported that mutation of RRK 6 to AAA 6 in MUC1 blocks heregulin-dependent nucleolar targeting of MUC1 and ␥-catenin and redirects both proteins to the cytoplasm (26 (86). Mutation of target Cys residues can (i) modulate exit from the endoplasmic reticulum (69,87), (ii) alter steady-state subcellular localization (70,78), (iii) alter specific membrane trafficking steps (66,68,77,81,87), (iv) alter homotypic and heterotypic protein-protein interactions (72,84,88), (v) alter the association with lipid microdomains (82,89), or (vi) alter protein function (71,87,90,91).…”
Section: Muc1 Exhibits Dual Palmitoylation At the Boundary Of The Tramentioning
confidence: 99%
“…MDCK1 cells expressing MUC1 with 15 tandem repeats were prepared by transduction with a recombinant retrovirus and cloning by limiting dilution as described previously (6,43). MUC1 with 22 tandem repeats was also subcloned into pcDNA3-neo (Invitrogen) for transient expression of MUC1 or MUC1 mutants in CHO cells by infection with recombinant vaccinia virus (vT7CP) and transfection with plasmids using Lipofectamine reagent (Invitrogen) as described previously (44).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The granins are very hydrophilic proteins with a high proportion of charged, mostly acidic, amino acid residues, and they all have some adjacent basic residues that are potential sites for proteolytic processing to smaller, perhaps biologically active, peptides (Holthuis et al 1996;Muller et al 1997). Chromogranin and/or secretogranin family members are often concentrated in the matrix of secretory granules.…”
Section: Introductionmentioning
confidence: 99%